Little Blue Truck's Halloween : a lift-the-flap book - Schertle, Alice; McElmurry, Jill (Boston, Massachusetts : Houghton Mifflin Harcourt, 2016)
Little Blue Truck and his friend Toad pick up their animal friends for a Halloween costume party and attempt to guess the identities of the dressed-up passengers, in a story complemented by interactive lift-flaps.
Cover title.
Keywords: Lift-the-flap books -- Specimens; Board books; Trucks -- Fiction; Halloween -- Fiction; Holidays -- Fiction; Stories in rhyme; Lift-the-flap books; Toy and movable books; Board books; Trucks -- Fiction; Halloween -- Fiction; Holidays -- Fiction; Toy and movable books; Board books for children; Stories in rhyme